Wireless Capsule Endoscopy for Obscure Gastrointestinal Bleeding: Single Center, One Year Experience - Shou-jiang Tang; Dimitrios Christodoulo; Simon Zanati; Elena Dubcenco; Rima Petroniene; Maria Cirocco; Gabor Kandel; Gregory B Haber; Paul Kortan; Norman E Marcon (Canadian Journal of Gastroenterology)
BACKGROUND: Wireless capsule endoscopy (CE) is increasingly being used in the investigation of obscure gastrointestinal (GI) bleeding, but some studies have found that many of the bleeding lesions recognized by this technique are within the reach of conventional endoscopy.